Green Supply Chain Management in the Malaysian Automotive Industry: A Systems Thinking Perspective - Noor Sufiawati Khairani; Eley Suzana Kasim; Indra Devi Rajamanoharan; Faridah Najuna Misman (International Journal of Supply Chain Management, 2017)
This study examines the deployment of green supply chain management (GSCM) in the Malaysian automotive industry. Proponents of GSCM suggest that as an advanced corporate environmental governance practice, GSCM is an important corporate strategy deployed for sustainability particularly in the automotive industry. However, little is understood about the deployment of GSCM within an automotive industry operating in a developing country like Malaysia. The present study addresses this literature gap by focusing on both the GSCM deployment procedures and practices within the Malaysian automotive industry. The study adopts a qualitative research methodology, with data collected through semi-structured interviews, observation and document reviews from a single automotive manufacturing case firm operating in Malaysia. Consistent with the literature, our findings suggest that the case firm uses a holistic and systemic approach to deploy GSCM practices. This holistic GSCM deployment approach involves a structured regulated procedureled method that directly supports systemic green practices.